2019
DOI: 10.1002/bies.201800226
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Resistance in Coral Reef Ecosystems: The Interplay of Biophysical Factors and Bleaching Resistance under a Changing Climate

Abstract: If we are to ensure the persistence of species in an increasingly warm world, of interest is the identification of drivers that affect the ability of an organism to resist thermal stress. Underpinning any organism's capacity for resistance is a complex interplay between biological and physical factors occurring over multiple scales. Tropical coral reefs are a unique system, in that their function is dependent upon the maintenance of a coral-algal symbiosis that is directly disrupted by increases in water tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 115 publications
(215 reference statements)
1
35
0
Order By: Relevance
“…For example, regions of higher mixing and temporal thermal respite have be found to result in lower mortality in benthic invertebrates and habitat‐forming organisms (Baird et al, ; Frade et al, ; Green et al, ; Richards et al, ; Roberts et al, ). These examples support the assertion that regions characterized by high thermal variance, and those with short‐term respite during extremes, have greater capacity to withstand extreme conditions (Ainsworth et al, ; Castillo, Ries, Weiss, & Lima, ; Klein et al, ; Morikawa & Palumbi, ; Page et al, ).…”
Section: What Can We Learn From Recent Climate Extremes?supporting
confidence: 61%
“…For example, regions of higher mixing and temporal thermal respite have be found to result in lower mortality in benthic invertebrates and habitat‐forming organisms (Baird et al, ; Frade et al, ; Green et al, ; Richards et al, ; Roberts et al, ). These examples support the assertion that regions characterized by high thermal variance, and those with short‐term respite during extremes, have greater capacity to withstand extreme conditions (Ainsworth et al, ; Castillo, Ries, Weiss, & Lima, ; Klein et al, ; Morikawa & Palumbi, ; Page et al, ).…”
Section: What Can We Learn From Recent Climate Extremes?supporting
confidence: 61%
“…Here, we found that the reef with the greatest water flow, diel physicochemical variation, and distance from land resulted in higher coral growth and fitness. Sufficient water flow is generally beneficial for coral performance across reef systems ( 70 ), and both flow and temperature variability can mitigate bleaching responses ( 21 , 36 , 70 ), indicating that these may be generalizable environmental characteristics of reefs that promote coral fitness and bleaching resistance (although, for exception, see ref. 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…loss, expansion and fragmentation of seagrass beds, kelp beds, saltmarshes, and mangroves) (Halpern et al 2019). Across the global tropics, remote sensing data from air-and space-borne sensors have revealed the complex spatial and temporal patterns in the biological responses of corals to marine heat waves (Page et al 2019). Such complex changes emerging at multiple scales justify the application of pattern-oriented scientific methods in attempts to understand and predict the consequences of changing seascape structure on ecological functions (Wu 2019, Bryan-Brown et al 2020 and to identify spatial threshold effects (Yeager et al 2016, Santos et al 2018.…”
Section: How Seascape Ecology Can Help Address Applied Research Challengesmentioning
confidence: 99%